Glyphosate and neurological outcomes: A systematic literature review of animal studies. (19th May 2022) - Moser, Virginia C; Morris-Schaffer, Keith; Richardson, Jason R; Li, Abby A
ABSTRACT: Studies of nervous system effects of glyphosate, a widely used herbicide, have not been critically examined. The aim of this paper was to systematically review glyphosate-induced neurotoxicity literature to determine its usefulness in regulatory decision-making. The review was restricted to mammalian studies of behavior, neuropathology, and neuropharmacology; in vitro and other biochemical studies were considered supplementary information. Glyphosate formulation studies were also considered, despite uncertainties regarding toxicities of the formulated products; no studies used a formulation vehicle as the control. Inclusion criteria were developed a priori to ensure consistent evaluation of studies, and in vivo investigations were also ranked using ToxRTool software to determine reliability. There were 27 in vivo studies (open literature and available regulatory reports), but 11 studies were considered unreliable (mostly due to critical methodological deficiencies). There were only seven acceptable investigations on glyphosate alone. Studies differed in terms of dosing scenarios, experimental designs, test species, and commercial product. Limitations included using only one dose and/or one test time, small sample sizes, limited data presentation, and/or overtly toxic doses. While motor activity was the most consistently affected endpoint (10 of 12 studies), there were considerable differences in outcomes. In six investigations, there were no marked neuropathological changes in the central or peripheral nervous system. Other neurological effects were less consistent, and some outcomes were less convincing due to influences including high variability and small effect sizes. Taken together, these studies do not demonstrate a consistent impact of glyphosate on the structure or function of the mammalian nervous system.